Implementation of cervical cancer prevention and screening at global and national levels: a review of evidence and research gaps - Dhital, Rolina; Dangal, Ganesh; Gopali, Lovin; Rimal, Reshika; Dwa, Yam Prasad; Poudel, Sandesh (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To identify the existing solutions and research gaps globally and in Nepal to provide an overview on the existing solutions and research gaps. Methods: Different databases such as PubMed, Google Scholar, registries, and relevant organizational websites were searched. The study designs included systematic reviews on cervical cancer prevention and screening globally and original studies and program related reports in Nepal. Narrative summary of the findings were performed. Results: Globally, most of the systematic reviews are conducted in low and middle-income countries followed by high-income countries. The cost-effective and common interventions globally and in South Asia includes awareness and educational activities for cervical cancer screening and prevention, early medical interventions such as pap smears, HPV vaccination, and visual inspection with acetic acid. Barriers to cervical cancer screening include lack of education, low socioeconomic status, and lack of knowledge, lack of effective communication, embarrassment, time constraints, and preference of female doctors. In Nepal, the national guidelines on cervical cancer screening and prevention were published more than a decade ago. The published studies indicated a low level of knowledge and attitude related to cervical cancer prevention and screening. Conclusions: Research in cervical cancer prevention and screening has received recognition globally in recent years. In Nepal, research that has explored the implementation and policy gaps at a deeper level through different dimensions remain inadequate. The findings of this review could pave way for designing better studies for sustainable interventions in the long run.